Coconut Water: A Sports Drink Alternative? - Brendan J. O’Brien; Leo R. Bell; Declan Hennessy; Joshua Denham; Carl D. Paton (Sports, 2023)
Coconut water is used as an alternative to conventional sports drinks for hydration during endurance cycling; however, evidence supporting its use is limited. This study determined if drinking coconut water compared to a sports drink altered cycling performance and physiology. In a randomized crossover trial, 19 experienced male (n = 15) and female (n = 4) cyclists (age 30 ± 9 years, body mass 79 ± 11 kg, <semantics><mover accent="true">V̇</mover></semantics>O2 peak 55 ± 8 mL·kg−1·min−1) completed two experimental trials, consuming either a commercially available sports drink or iso-calorific coconut water during 90 min of sub-maximal cycling at 70% of their peak power output, followed by a simulated, variable gradient, 20 km time trial. Blood glucose, lactate, sweat loss, and heart rate were monitored throughout the 90 min of sub-maximal cycling, as well as the time trial performance (seconds) and average power (watts). A repeated measures analysis of variance and effect sizes (Cohen’s d) analysis were applied. There were no significant differences (p ≥ 0.05) between the treatments for any of the measured physiological or performance variables. Additionally, the effect size analysis showed only trivial (d ≤ 0.2) differences between the treatments for all the measured variables, except blood glucose, which was lower in the coconut water trial compared to the sports drink trial (d = 0.31). Consuming coconut water had a similar effect on the cycling time trial performance and the physiological responses to consuming a commercially available sports drink.